A genotype-specific architectural and physiological profile is involved in the flowering regularity of apple trees. (11th August 2022) - Belhassine, Fares; Pallas, Benoît; Pierru-Bluy, Sylvie; Martinez, Sébastien; Fumey, Damien; Costes, Evelyne
Abstract: In polycarpic plants, meristem fate varies within individuals in a given year. In perennials, the proportion of floral induction (FI) in meristems also varies between consecutive years and among genotypes of a given species. Previous studies have suggested that FI of meristems could be determined by the within-plant competition for carbohydrates and by hormone signaling as key components of the flowering pathway. At the genotypic level, variability in FI was also associated with variability in architectural traits. However, the part of genotype-dependent variability in FI that can be explained by either tree architecture or tree physiology is still not fully understood. This study aimed at deciphering the respective effect of architectural and physiological traits on FI variability within apple trees by comparing six genotypes with contrasted architectures. Shoot type demography as well as the flowering and fruit production patterns were followed over 6 years and characterized by different indexes. Architectural morphotypes were then defined based on architectural traits using a clustering approach. For two successive years, non-structural starch content in leaf, stem and meristems, and hormonal contents (gibberellins, cytokinins, auxin and abscisic acid) in meristems were quantified and correlated to FI within-tree proportions. Based on a multi-step regression analysis, cytokinins and gibberellins content in meristem, starch content in leaves and the proportion of long shoots in tree annual growth were shown to contribute to FI. Although the predictive linear model of FI was common to all genotypes, each of the explicative variables had a different weight in FI determination, depending on the genotype. Our results therefore suggest both a common determination model and a genotype-specific architectural and physiological profile linked to its flowering behavior.